1996
DOI: 10.1111/j.1460-9592.1996.tb00435.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthesia and the Beckwith‐Wiedemann syndrome

Abstract: Infants with Beckwith-Wiedemann syndrome usually present different abnormalities which may require surgical correction. Anaesthetic management may be complicated by abnormal airway anatomy, congenital heart disease and severe hypoglycaemia. Careful preoperative evaluation, perioperative monitoring and suitable choice of anaesthetic technique are required for a successful outcome. We report the perioperative management of a patient with Beckwith-Wiedemann syndrome presenting for omphalocoele surgery on his firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Beckwith-Wiedemann syndrome is caused by mutations in the genes; the prevalence of this condition is 1 per 13,700-15,000 births, with equal sex distribution [ 3 4 5 6 ]. Clinical features of the syndrome include macroglossia, omphalocele, umbilical hernia, and neonatal hypoglycemia [ 4 5 6 7 ]. Macroglossia is especially associated with Beckwith-Wiedemann syndrome in 95% of the patients [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beckwith-Wiedemann syndrome is caused by mutations in the genes; the prevalence of this condition is 1 per 13,700-15,000 births, with equal sex distribution [ 3 4 5 6 ]. Clinical features of the syndrome include macroglossia, omphalocele, umbilical hernia, and neonatal hypoglycemia [ 4 5 6 7 ]. Macroglossia is especially associated with Beckwith-Wiedemann syndrome in 95% of the patients [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was first described by Beckwith in 1963 and later substantiated by Wiedemann in 1964 [ 1 2 3 ]. Macroglossia is a condition observed in patients with this syndrome, and is associated with difficult perioperative anesthetic management [ 4 5 6 ]. It has been reported that perioperative anesthetic management might be complicated by anatomical airway abnormalities [ 1 2 3 4 5 6 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal airway anatomy, congenital heart disease and severe hypoglycemia [19, 20]may complicate anesthetic procedures. Craniofacial anomalies, as observed in the present case, often aggravate endotracheal intubation.…”
Section: Discussionmentioning
confidence: 99%
“…The Beckwith–Wiedemann syndrome (BWS) has as its essential features omphalocele, macroglossia, hypoglycaemia, inguinal hernia with gigantism, organomegaly, renal medullary dysplasia, cardiac defects and embryonal tumours occurring less frequently ( 1). Anaesthetic management in children with the BWS ( 2) may be complicated by a potentially difficult airway ( 3–9). The laryngeal mask airway (LMA) may afford airway patency when we are faced with abnormal anatomy and troublesome intubation.…”
Section: Introductionmentioning
confidence: 99%